Taking Heed: Principals Who Identify as African American or Black Working in Predominantly White Schools - (:unkn) unknown (My University, 2019)
This is a narrative study of the lived experiences of school leaders who identify as African American or Black and are working in predominately White school settings. The study sought to understand the lived experiences of these school leaders by exploring how these leaders make sense of their work in a predominantly White setting. This included the opportunities and challenges they encountered and the leadership beliefs, practices, and strategies they employed to navigate the predominantly White school setting. A critical race methodology was used throughout the study that centered race and racism in all aspects of the research (Solórzano & Yosso, 2002). This was important to the study as predominantly White school settings are racialized organizations that seek to marginalize students and educators of color learning and working in their organizations (Ray, 2019). Data was gathered using interviews which generated narratives for each of the ten participants. A thematic data analysis of the narratives resulted in eight common themes with related sub themes. The six findings of the study are focused on elevating the voices of the ten school leader participants who are African American or Black to an audience of White district leaders that are called upon to disrupt their predominantly White organizations so that all children receive an equitable education.
Keywords: Critical Race Methodology; Educational leadership; Lived Experiences; Predominantly White Schools; Principals who are African American; School Leaders who are African American